What Should Be the Surgical Technique for Treating Thin Melanoma? - Yu, Wesley Y.; Bordeaux, Jeremy S. (NEJM Evidence, 2023)
Surgical techniques with complete margin assessment (e.g., Mohs surgery, staged excision with permanent sections) allow pathologic examination of the entire marginal surface of a cancer excision specimen. Compared with conventional wide excision, complete margin assessment may reduce sampling error when evaluating margin status, allow for more rapid surgical clearance of positive margins, and minimize surgical defect size in anatomically constrained locations (e.g., face, hands, feet, genitals). Prospective data comparing the safety and efficacy of complete margin assessment and conventional wide excision in the treatment of melanoma are lacking. This article reviews the evidence and proposes a trial to address the question: Which is the better surgical method for treating thin invasive melanoma and melanoma in situ in high-risk anatomical locations?